RACISM: FIGHT IT OR LET IT BE - Tesya Shifa Saputi; Muhammad Iqbal; Seno Dilogo (Universitas Duta Bangsa Surakarta, 2020)
Racism is happening in the world today is getting worse. with the death of George Floyd, acitizen of the United States who died because of his neck was detained by white police, on the charge thathe was a dealer in counterfeit money. the incident sparked strong condemnation from all over the world.racism has occurred since ancient times, even though the colonial era. where black people, who came fromAfrica, many were made slaves by their white masters. they do not get their full rights. The spread of casesof persecution, insults, insults, injustice for those who are black, really makes justice unfair. There havebeen many community leaders, artists, and the government have also done various ways to eliminate thestigma of black people are criminals. However, this is almost impossible because racism has taken root inthe sphere of people's lives.